ISO 9001 and ISO/IEC 17025 which is the best option for a laboratory of metrology? The Portuguese experience - Barradas, José (2017)
Purpose - According to the ISO 9001 standard, all the certified companies should calibrate their measuring equipment. By doing so, companies can guarantee, with rigor and quality, its measurement and use reliable data for monitoring the quality of their products. However, a metrology laboratory is not required to have an ISO 9001 certification or ISO/IEC 17025 accreditation. At this moment, there are companies with their quality management systems certified according to the ISO 9001 standard which have metrology laboratories to make internal checks of their measuring equipment. On the other hand, there are companies with ISO/IEC 17025-accredited laboratories. Finally, there are companies that have their QMS certified according to ISO 9001 and also their metrology laboratory accredited by ISO/IEC 17025. In this case the metrology laboratory must comply with the requirements of both standards. Thus, the purpose of this paper is to analyze the level of importance of the ISO 9001 and ISO/IEC 17025 standards from the perspective of a metrology laboratory.Design/methodology/approach - The research methodology used to conduct this research was supported in case studies that had been carried out in nine metrology laboratories. The information was gathered based on semi-structured interviews.Findings - After an analysis and discussion over the data obtained, the authors verified that the impact on customer perception is significantly positive, if the metrology laboratory is simultaneous certified and accredited.Originality/value - From the laboratories perspective, the issue analyzed in this paper is of the utmost importance and the aim is to give the contribution in order to clarify this kind of organizations of which could be the best option for their context.